A pilot clinical validation study of a self-collected vaginal swab device for the detection of chlamydia trachomatis in women - Muljadi, Michael; Cheng, Chao-Min; Yang, Chung-Yao; Chang, Ting-Chang; Shen, Ching-Ju (Frontiers in Bioengineering and Biotechnology, 2022)
Chlamydia trachomatis (C. trachomatis) is one of the most prevalent sexually transmitted diseases (STDs) in the world. In women, C. trachomatis infection can lead to long-term complications such as pelvic inflammatory disease (PID), and others such as ectopic pregnancies and tubal factor infertility. These complications are preventable given early detection and clinical intervention, but these efforts are often hampered by asymptomatic infections, and non-compliance to screenings. Some women do not get tested out of concerns for violation of privacy, and fear of discomfort. Clinicians often use a multitude of tests to determine if a patient is infected by Chlamydia, including a Polymerase Chain Reaction (PCR) test of First catch urine (FCU) samples. However, these tend to be inconvenient to store and transport, as they carry risk of spillage and have stringent refrigeration requirements. The current study therefore looks at the potential of a self-collected vaginal swab device that relies on Nucleic Acid Amplification Tests (NAATs), is dry-stored, and does not require refrigeration, to detect the presence of Chlamydia in women. The study found evidence to suggest that the device has potential to aid clinicians in Chlamydia diagnosis in women when compared to doctor-collected vaginal discharge samples as the designated standard, FCU, and blood serology. Moreover, as a self-collection device it has the potential to break down some of the barriers to STD screening especially in young women. The device therefore has potential to encourage screening and therefore a potentially effective tool in the fight against the spread of preventable STDs.